The Satyagraha of John Brown - Braatz, Timothy (In Factis Pax: Journal of Peace Education and Social Justice, 2014)
ohn Brown, a complicated man with the plainest of names, lives on—or so we are told.1 The past decade or so has seen a resurgence of scholarly interest in his remarkable life, due in part to a combination of the sesquicentennial of his Harpers Ferryraid, a handful of recent high-profile acts of terrorism within U.S. borders, and one well- received novel.2 In popular memory, Brown is known for taking an unwavering stand against the evil of slavery, to the point of killing civilians who stood in his way. Accounts of his life typically begin with the dramatic raid—no surprise in a culture that celebrates the gunfighter archetype. In academic circles, Brown serves as the centerpiece of discussions regarding the use of violence for moral ends.